Current prevalence and therapeutic strategies for porcine Streptococcus suis in China - Lv, Ruoyi; Zhang, Wenjing; Sun, Zhigang; Si, Xiaohui; Dong, Hong; Liu, Xiaoye (Applied and environmental microbiology, 2025)
Porcine is a zoonotic bacterial pathogen that poses serious threats to both human and animal health. is ubiquitously transmitted from the swine industry to the environments and human communities. However, the ambiguous epidemiological patterns and the escalating risk of antimicrobial resistance render infections a considerable challenge. Here, we review the current prevalence of infection worldwide, including identified bacterial strains, routes of infection, and transformation of resistance genes. This comprehensive overview of the prevalent patterns in offers detailed insights into therapeutic approaches for porcine infections and alternative strategies to address emerging resistant strains, highlighting potential multitarget prevention and treatment options to combat infection.